Novel unsteady temperature/ heat transfer instrumentation and measurements in the presence of combustor instabilities - Chana, K; Syed, K; Wedlock, M; Copplestone, R; Cook, MS; Bulat, G (2005)
Lower NOx emissions from gas turbine combustion systems can be achieved through reducing the equivalence ratio of the main reaction zone and/or increasing the burner pressure drop. This strategy however takes pressure drop and/or air away from the combustor cooling, thereby compromising the combustor life. In order to achieve an optimum design that is a good compromise between low emissions and long component life, accurate heat transfer prediction is essential. It is well known that free stream turbulence can influence wall heat transfer characteristics. However the impact of combustion induced pressure dynamics, and the associated unsteady fluid dynamics, upon combustor wall heat transfer has not been adequately investigated. This paper reports on combustion tests conducted at gas turbine operating conditions, where pressure dynamics have been controlled by altering combustor operating conditions and through the use of a siren placed in the upstream air flow. Combustor wall temperatures were measured using standard thermocouples and QinetiQ's "True Surface Thermocouples" (TST). The latter, which were mounted on the hot gas surface of the wall, are capable of a fast response and are capable of indicating the temperature fluctuations experienced by the metal surface. Fourier analysis of the TSTs showed no particular peaks associated with the pressure dynamics. This suggests that any coherence is damped within the boundary layer or by the thermal inertia of the metal. However temperature fluctuations of up to about 100°C were detected. Copyright © 2005 by ASME.